Land, Property & Construction in the People's Republic of China - Walker, Anthony, 1939- (Book collections on Project MUSE., 1991)
China's struggle to develop its economy and improve the material well being of its population has been in progress since the end of the Cultural Revolution and has gathered momentum since 180. Important facets of China's "modernization" have been the reform of land policies, the improvement of efficiency of the construction industry and the attraction of foreign investment. These three aspects are closely linked in providing the infrastructure and building assets required by mature and progressive economies. China has a long way to go to, but it is clear that the role of land and construction in this process is fully understood. Translating this understanding into reality, however, requires a level of application that is often difficult to achieve.